Pengalaman Ibu yang Merawat Remaja Skizofrenia Pasca Rawat Inap - Chatarina Suryaningsih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to explore the experience of mothers caring for schizophrenic adolescents after hospitalization. This type of research is qualitative research with a descriptive phenomenological approach. The results of this study indicate that the participants who took part in this study consisted of 7 mothers who cared for adolescent children with schizophrenia, with an age range of 39 years to 57 years. Most of the participants were housewives, and the education level of the participants was from elementary to high school. All participants had schizophrenic teenagers at home. The participant's residence is in the Bandung area. In conclusion, this study resulted in six themes, namely psychological responses during caring for children, support received by mothers to continue treatment of children, disturbances in daily activities, treatment efforts made by mothers to heal their children, coping strategies while caring for children, stigma felt by mothers during treatment. Take care of children. Keywords: Mother's Experience, Schizophrenic Adolescents